Validation of the quality of life multiple myeloma module questionnaire (QLQ‐MY20) in portuguese myeloma patients - Pereira, M. Graça (2019)
Objective:The aim of this study was the validation of the European Organization for Research and Treatment of Cancer's Multiple Myeloma Module (QLQ‐MY20) in Portuguese myeloma patients. Methods: A total of 213 Portuguese patients diagnosed with multiple myeloma participated in this study and were assessed with the European Organization for Research and Treatment of Cancer's (EORTC) Questionnaire C30 (QLQ‐C30), the EORTC Multiple Myeloma Module (QLQ‐MY20), the Hospital Anxiety and Depression Scale (HADS) and the Satisfaction with Social Support Scale (SSSS). Results: The validated version includes 17 items presenting good global adjustment and good internal consistency. Overall, the Portuguese validation maintains the original model with the exception of three items that were excluded. The instrument also showed good reliability and good convergent and divergent validity. Conclusion: The Portuguese version of the EORTC Multiple Myeloma Module questionnaire seems to be a valid instrument for myeloma patients to help monitor interventions in this population focused on the promotion of quality of life.